Bilateral internal carotid artery hypotrophy in malignant osteopetrosis - Ramli, N.; Rahmat, K.; Tan, G.P. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
Malignant osteopetrosis is associated with petrous carotid canal and internal carotid artery stenosis in the skull base. We present a four-year-old boy with malignant osteopetrosis who developed right frontal lobe infarction as a result of bilateral internal carotid artery hypotrophy.